Cost‐Effectiveness of Interventions for Musculoskeletal Foot and Ankle Conditions: A Systematic Review. Issue 4 (9th March 2022) - Walsh, Tom P.; Merlo, Greg B.; Rutter, Cameron; Abell, Bridget; Platt, Simon R.; Arnold, John B.
Abstract : Objective: Musculoskeletal conditions of the foot and ankle are common, yet the cost‐effectiveness of the variety of treatments available is not well defined. The aim of this systematic review was therefore to identify, appraise, and synthesize the literature pertaining to the cost‐effectiveness of interventions for musculoskeletal foot and ankle conditions. Methods: Electronic databases were searched for studies presenting economic evaluations of nonsurgical and surgical treatments for acute or chronic musculoskeletal conditions of the foot and ankle. Data on cost, incremental cost‐effectiveness, and quality‐adjusted life years for each intervention and comparison were extracted. Risk of bias was assessed using the Drummond checklist for economic studies (range 0–35). Results: Thirty‐six studies were identified reporting nonsurgical interventions (n = 10), nonsurgical versus surgical interventions (n = 14), and surgical interventions (n = 12). The most common conditions were osteoarthritis, ankle fracture, and Achilles tendon rupture. The strongest economic evaluations were for interventions managing end‐stage ankle osteoarthritis, ankle sprain, ankle fracture, calcaneal fracture, and Achilles tendon rupture. Total ankle replacement and ankle arthrodesis for end‐stage ankle osteoarthritis, in particular, have been demonstrated through high‐quality studies to be cost‐effective compared to the nonsurgical alternative. Conclusion: Selected interventions for musculoskeletal foot and ankle conditions dominate comparators, whereas others require thoughtful consideration as they provide better clinical improvements, but at an increased cost. Researchers should consider measuring and reporting costs alongside clinical outcome to provide context when determining the appropriateness of interventions for other foot and ankle symptoms to best inform future clinical practice guidelines.